2017
DOI: 10.1002/anie.201702558
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Approach to Inorganic Phosphazane Macrocycles

Abstract: Inorganic macrocycles, based on non-carbon backbones, present exciting synthetic challenges in the systematic assembly of inorganic molecules, as well as new avenues in host-guest and supramolecular chemistry. Here we demonstrate a new high-yielding modular approach to a broad range of trimeric and hexameric S- and Se-bridged inorganic macrocycles based on cyclophosphazane frameworks, using the building blocks [S=(H)P(μ-NR)] . The method involves the in situ generation of the key intermediate [E....._ (S....._… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 46 publications
2
22
0
1
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28][29] Of particular interest is the pentameric host macrocycle 1 (Figure 1), toroidal shape,l arge void volume, endo-cyclic N-H functionalities,a nd exo-cyclic t Bu groups of which make it ahighly unusual, sterically hindered H-bonding host. [20][21][22][23][24][25][26][27][28][29] Of particular interest is the pentameric host macrocycle 1 (Figure 1), toroidal shape,l arge void volume, endo-cyclic N-H functionalities,a nd exo-cyclic t Bu groups of which make it ahighly unusual, sterically hindered H-bonding host.…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29] Of particular interest is the pentameric host macrocycle 1 (Figure 1), toroidal shape,l arge void volume, endo-cyclic N-H functionalities,a nd exo-cyclic t Bu groups of which make it ahighly unusual, sterically hindered H-bonding host. [20][21][22][23][24][25][26][27][28][29] Of particular interest is the pentameric host macrocycle 1 (Figure 1), toroidal shape,l arge void volume, endo-cyclic N-H functionalities,a nd exo-cyclic t Bu groups of which make it ahighly unusual, sterically hindered H-bonding host.…”
mentioning
confidence: 99%
“…Due to interesting applications of derivatives like [ClP(=E)(µ‐NR)] 2 (E = S, Se) and very limited information being available on the mixed‐valent P III /P V species, [(E=)ClP(µ‐N t Bu) 2 PCl], the oxidations of [ClP(µ‐N t Bu)] 2 with S and Se were performed and monitored by in situ 31 P{ 1 H} NMR spectroscopy, with the aim of determining whether the synthesis of monochalcogenido P III /P V species can be controlled and whether they are intermediate compounds towards [ClP(=E)(µ‐NR)] 2 (E = S, Se). It has been observed that the reaction of [ClP(µ‐N t Bu)] 2 with an equivalent amount of selenium in boiling toluene takes ca.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, it is necessary to stabilise the P 2 N 2 units of [ 11 ‐ t Bu] 2− prior to cyclisation, by oxidation of the P‐centers with elemental S or Se (Scheme ), producing the new P V dianions [(E)(S)P(μ‐N t Bu] 2 2− [E=S ( 16 a ), Se ( 16 b )] (Scheme ). This approach provides the basis for a modular, one‐pot synthesis of a range of S‐ and Se‐bridged macrocycles . Deprotonation of 11 H 2 ‐ t Bu (most conveniently with PhCH 2 Na), followed by room‐temperature in situ oxidation with S or Se, then addition of a range of dichlorides [ClP(μ‐NR)] 2 gives the macrocycles 17 (E=S; R= t Bu, neopentyl, R ‐1‐(2‐napthyl)ethyl) or 18 (E=Se; R= t Bu) in isolated yields of over 80 %, having (P III ) 2 (P V ) 2 backbones (Scheme ).…”
Section: Isoelectronic Nucleophilic Precursors‐group 16 Bridged Macromentioning
confidence: 99%
“…The solid‐state structure of 17 ‐ t Bu is shown in Figure a . The all‐ cis arrangement of the constituent P 2 N 2 ring units can be compared to the all‐ trans arrangement found in the structurally related Sb III macrocycle 1 (Figure ).…”
Section: Isoelectronic Nucleophilic Precursors‐group 16 Bridged Macromentioning
confidence: 99%
See 1 more Smart Citation